MODEL PEMBERDAYAAN EKONOMI BERBASIS COMMUNITY-BASED TOURISM BAGI MASYARAKAT DESA DI SEKITAR KAWASAN NUSA DUA - I Made Sujana; Fahmi Tanjung; Putu Ratna Windusara Putri; Ni Luh Wulani Parwati (Yayasan Nusantara Hasana Berdikari, 2024)
The rapid growth of tourism in Nusa Dua, Bali, has contributed significantly to regional economic development. However, the benefits of tourism are not always distributed evenly among communities living in surrounding villages. This study aims to formulate a Community-Based Tourism (CBT)-based economic empowerment model for village communities around the Nusa Dua tourism area. The research employed a qualitative descriptive approach through observations, interviews, focus group discussions, and document analysis involving village officials, tourism actors, local business groups, and community leaders. The findings reveal that community participation, institutional strengthening, local entrepreneurship development, digital marketing, and collaboration among stakeholders are key components of sustainable economic empowerment. The proposed model integrates community participation, local resource optimization, institutional support, and sustainable tourism governance. This model is expected to improve community welfare, increase local economic resilience, and strengthen the competitiveness of tourism villages surrounding Nusa Dua.